1985
DOI: 10.1002/art.1780280106
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic value of graded aerobic exercise training in rheumatoid arthritis

Abstract: Women with rheumatoid arthritis performed 1 of 3 low intensity aerobic exercise protocols (15,25, and 35 minutes) 3 times per week for 12 weeks. A nontraining group served as controls. All exercise groups improved their aerobic capacity, exercise time, and joint counts. Subjects described improvement in activities of daily living and reduced joint pain and fatigue. Exercise duration up to 35 minutes can be therapeutic, and as little as 15 minutes of exercise 3 timedweek is sufficient to improve aerobic capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(89 citation statements)
references
References 10 publications
3
85
0
1
Order By: Relevance
“…No studies reported worse outcomes for function, disease activity or aerobic capacity with dynamic exercise. Some studies also reported improvements in disease activity measures 15,19,20,25 , and small improvements in hip bone mineral density. 13,16 One study reported significantly less progression of small joint radiographic damage of the feet in the dynamic exercise group.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…No studies reported worse outcomes for function, disease activity or aerobic capacity with dynamic exercise. Some studies also reported improvements in disease activity measures 15,19,20,25 , and small improvements in hip bone mineral density. 13,16 One study reported significantly less progression of small joint radiographic damage of the feet in the dynamic exercise group.…”
Section: Discussionmentioning
confidence: 98%
“…Harckom et al 20 studied 20 women with RA aged 27-68 years, of ARA functional class II for 12 weeks. Four intervention groups (3 exercise, 1 control) were used.…”
Section: Aerobic Exercisesmentioning
confidence: 99%
“…The type of PA included in the interventions varied, and included aerobic exercise 30 32,38 . In one study the control arm also performed range of movement and stretching exercises alongside usual recreational PA 29 .…”
Section: Type Of Physical Activitymentioning
confidence: 99%
“…Aerobic exercise intensity was targeted at 70-90% maximum heart rate in three studies 27,30,31 . Two studies reported a more general target of light-to moderate-intensity walking, where participants felt moderately short of breath 38 , or moderate-to vigorous-intensity aerobic PA 39 .…”
Section: Intensity Of Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation